2008
DOI: 10.1139/b07-128
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast DNA polymorphism reveals geographic structure and introgression in theQuercus crassifolia ×Quercus crassipeshybrid complex in Mexico

Abstract: Quercus crassifolia H. & B. and Quercus crassipes H. & B. are two common temperate forest species in Mexico that form hybrids when they occur in mixed (sympatric) areas. In this study, we used chloroplast microsatellite haplotypes to infer phylogeographic patterns onto the genetic structure of populations of both parental species, thus defining probable colonization routes throughout Mexico. Haplotype diversity in seven hybrid zones and four allopatric sites with nonmixed (allopatric) populations of bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 62 publications
2
18
0
1
Order By: Relevance
“…This is because many oak species can be considered foundation species due to their wide geographic distribution (Valencia 2004) and dominance in the canopy of forests (TovarSánchez et al 2013) and because they are habitat to different species. They also show a high frequency of natural hybridization (Curtu et al 2007;Peñaloza-Ramírez et al 2010;Valencia-Cuevas et al 2015), a condition that can promote an increase in genetic diversity (Tovar-Sánchez et al 2008;Valencia-Cuevas et al 2014) and the appearance of new features in host plants (Tovar-Sánchez and Oyama 2004) which can be exploited by arthropod communities. However, to date, there are few studies that have evaluated the structure of arthropod communities associated with the canopy of oaks from a genetic perspective.…”
Section: Reviewmentioning
confidence: 99%
“…This is because many oak species can be considered foundation species due to their wide geographic distribution (Valencia 2004) and dominance in the canopy of forests (TovarSánchez et al 2013) and because they are habitat to different species. They also show a high frequency of natural hybridization (Curtu et al 2007;Peñaloza-Ramírez et al 2010;Valencia-Cuevas et al 2015), a condition that can promote an increase in genetic diversity (Tovar-Sánchez et al 2008;Valencia-Cuevas et al 2014) and the appearance of new features in host plants (Tovar-Sánchez and Oyama 2004) which can be exploited by arthropod communities. However, to date, there are few studies that have evaluated the structure of arthropod communities associated with the canopy of oaks from a genetic perspective.…”
Section: Reviewmentioning
confidence: 99%
“…Oaks (Fagaceae, Quercus) are an ideal system to study the effects of host-plant species genetic diversity on their associated canopy communities because of their high levels of genetic variation (e.g., Tovar-Sánchez et al 2008;Valencia-Cuevas et al 2014, 2015; many of their species show a wide geographical distribution and canopy dominance (Valencia 2004), and constitute the habitat of different species. Therefore, some of them can be considered as foundation species.…”
Section: Introductionmentioning
confidence: 99%
“…2004). Chloroplast DNA analyses revealed that for both species, colonization routes were in a north -south direction following the formation and retreat of glaciers during the Last Glacial Maximum (Tovar-Sánchez et al 2008). Quercus crassifolia colonized initially the northern part of SMOc, the entire FVT and the southern parts of SMOr.…”
Section: Methodsmentioning
confidence: 99%
“…Hybrid zones have been found between several Quercus species pairs (Tovar-Sánchez & Oyama 2004) and some authors have explored hybridization rates between three or more species of Quercus (Peñaloza-Ramírez et al 2010, Valencia-Cuevas et al 2014. Also, phylogeographical analyses have revealed a complex history of hybridization and introgression between oak species (González-Rodríguez et al 2004, Tovar-Sánchez et al 2008. Despite the high number of studies, the genus Quercus is still considered a "difficult" group for taxonomists.…”
mentioning
confidence: 99%